Aplicabilidade da teoria da cegueira deliberada na Administração Pública brasileira - Adolfs, Anderson da Silva (Brasil, 2019)
For the strengthening of a Republic, it is imperative that each member develops his role with diligence and probity. In public and private organizations, there are functions specifically designed to evaluate the procedures performed, to point out failures and errors, with the purpose of rectifying them and avoiding their recurrence (CASTRO, 2009). This paper studies a doctrine called "Willfull Blindness Doctrine" that has been increasingly applied by the Brazilian Courts, in the most varied branches of Law, concluding on whether or not to apply it to cases involving legal experts and studying the expansion of the doctrine to the governmental control and audit bodies.